Factors influencing Bachelor of Science in Clinical Medicine students performance in Clinical Officer Council Licensure examination, Kenya - Kuria, Eunice M.; Nyongesa, Margaret W.; Choge, Joseph K.; Boruett, Norbert (International Journal Of Community Medicine And Public Health, 2021)
Background: Clinical medicine program has recorded high rates of student’s enrolment to training while their performance in clinical officers’ council (COC) licensure examination remains variable. This study investigated performance of clinical medicine degree student’s in COC examinations by determining student characteristics, institutional and regulatory body factors in relation to performance. Methods: A retrospective study, using mixed method approach to collect data. A sample total of 427 of students was analyzed while cluster and purposive sampling were used for key informants interviewed. Quantitative data was converted from Microsoft excel to statistical package for the social sciences (SPSS) software version 26 and analysed. Odd ratio was used to measure strength of association between students,institutions and regulatoy body charateristics and performance with p<0.05 being considered significant. Qualitative data was transcribed for content analysis. Results: The results indicated that there was highly significant relationship among the performance of students in government and private institutions respectively (p<0.001) unlike faith-based institutions (p=0.292). Private institutions were 0.158 more likely to perform better than other institutions while government institutions were 5 times more likely to perform better than any other institutions. Conclusions: Age, mode of study and years of experience were found to be significant factors associated with performance while intergrity in marking was an important concern. The recommendations from the study are that training institutions continue upgrading program but factors contributing to low performances should be looked into. There is need to select experienced faculty to teach and set competency based licensure examination after internship.The study has demonstrated that results can be used to predict performance which are reliable for developing recruitment and examination policies.